Thermomechanical peridynamic analysis with irregular non-uniform domain discretization. (15th June 2018) - Hu, Yile; Chen, Hailong; Spencer, Benjamin W.; Madenci, Erdogan
Highlights: Non-uniform discretization and variable horizon in the solution of peridynamic equation of motion. Distribution of the strain energy associated with an interaction between two material points according to the volumetric ratio arising from the presence of non-uniform discretization and variable horizon. Removal of the requirement for correction of peridynamic material parameters due to surface effects. Verification against the benchmark solutions, and an application to predict thermally induced cracking in a nuclear fuel pellet. Abstract: Irregular non-uniform discretization of the solution domain in models based on peridynamic theory can improve computational efficiency by allowing local refinement and remove mesh bias effects on crack initiation and propagation. However, the use of such discretizations generally requires adjustment of the classical peridynamic material parameters and usage of a variable horizon which results in the so-called ghost force effect in the interactions between differing horizons. This study presents a generalization of the original bond-based and ordinary state-based peridynamic models to permit the use of irregular non-uniform domain discretizations, in which the strain energy and thermal potential associated with a bond between two material points is split into two parts based on volumetric ratios. This division is potentially different for each bond due to the presence of irregular non-uniform discretization. The validity and accuracy of this proposed approach is established using several benchmark examples, and its applicability to real engineering problems is demonstrated by modeling thermally induced cracking in a three-dimensional nuclear fuel pellet.